Topography and narrative in the ‘Danişmendname’ - Bekker-Nielsen, T. (Turkic Studies Journal, 2026)
The Danişmendname, “Book of Danişmend”, is one of the oldest preserved epics in the Turkish language and the only one to provide a narrative of events around the turn of the twelfth century, the time of the First Crusade. Its protagonist, Ahmed Danişmend (“the wise”) is a historical figure, but the accounts of his battles against the Byzantines are largely fictional, replete with hyperbole and embellished with loans from other epic traditions, even Christian hagiography. The text was composed about AD 1050 and first written down at the Selçuk court around AD 1175. On this occasion, a fictitious epilogue was added, establishing a link with the Selçuk dynasty. Similarly, a prologue has been added to link the story of Danişmend to that of the epic hero Sayyid Battal. The written version was further expanded and embellished by Arif Ali, governor of Tokat in the fourteenth century, who divided the text into chapters and added verse passages of his own making. Ali’s text formed the basis of all later manuscripts of the “Danişmendname”. Through a detailed case-by-case study of the topographical descriptions in the “Danişmendname”, this study demonstrates that contrary to the opinion of Irène Mélikoff (Irène Mélikoff, 1960), these do not derive from the pen of Arif Ali but formed part of the original composition. Secondly, by applying the concept of the “storyworld” as defined by Buket Kitapçı Bayrı (2020), the study aims to identify the homeland and the mental universe of the original poet. He seems to be familiar with the upper Iris valley around Tokat and Komana as well as the area within the triangle Çorum-Amasya-Turhal. Cankırı and Niksar are also described in terms which may derive from personal observation. The author has a soldier’s eye for the landscape and probably participated in military campaigns on the frontier between Byzantium and Islam. Most of the other cities mentioned in the epic – Malatya, Ankara, Samsun, Osmancık, Sinop, Kastamonu, etc. – are mere names, and there is no attempt at describing their site or appearance. Outside his home region, the author has no clear idea of the geography and consistently underestimates the distance to Malatya or Bagdad. We may conclude that the originator of the “Danişmendname” was a native of northern Anatolia, well versed in the traditions of local storytellers and the topography of his homeland, but with little knowledge or experience of the wider world.